How Do We Read in the Age of Intertextual Digitalism?Bibliography and webography - George NEAGOE (Diversitate si Identitate Culturala in Europa, 2025)
The study is a reflection about how reading practices, habits, attitudes and methods changed in the most recent context of digitalism. This type of digital globalization has many consequences on humanistic studies. The shift to Digital Humanities is uncertain due to the lack of critical approach. Digitizing is not the same as digitalizing. The literary critics and historians, the textual scholars, the researchers of manuscripts and rare books need to redefine their status. Reading with proficiency may be their opportunity to engage into debates. But there are voices who claim that computers are able to perform the same task. Literary reading extended its meaning since the beginning of digital fiction. The aim of Digital Humanities would be the progress of knowledge, neglecting that objective data is an intellectual construct. Every notion is debatable and fluid. It seems there is no cardinal point. The next question might be whether AI is endowed with volition and dubitative attributes.